Distal Extension Denture – Case Report and Overview - Yeung C; Leung KCM; Yu OY; Lam WYH; Wong AWY; Chu CH (Dove Medical Press, 2020)
Conson Yeung, Katherine Chiu Man Leung, Ollie Yiru Yu, Walter Yu Hang Lam, Amy Wai Yee Wong, Chun Hung Chu Faculty of Dentistry, The University of Hong Kong, Hong KongCorrespondence: Chun Hung ChuPrince Philip Dental Hospital, 3B26, 34 Hospital Road, Sai Ying Pun, Hong KongTel +852 2859 0287Email chchu@hku.hkAbstract: Replacing missing teeth distal to the last standing teeth with removable partial dentures poses considerable challenge to dentists. However, the insertion of implants turns a free-end saddle into a bounded saddle. Still, patients may not be able to accept implant insertions due to financial reasons, systemic medical conditions, local anatomical factors or complicated treatments involving surgery. Hence, patients with missing teeth often prefer to use removable partial dentures to improve their dental aesthetics and to restore their oral function. In this article, we use a clinical case to illustrate the clinical procedures required for the fabrication of a distal extension denture with good retention, support, stability, aesthetics and masticatory function. We also review the design for a clasp assembly on the abutment adjacent to the distal edentulous ridge.Keywords: distal extension denture, altered cast technique